The influence of specific training on explosive power in top athletes - Caramoci, A.; Ionescu, A. M.; Nica, A. S.; Mazilu, V. (The European Proceedings of Social & Behavioural Sciences EpSBS, 2018)
Explosive power is an important aspect in sports events such jumping and throwing as well as in other sports like tennis, boxing, wrestling and most sports games. To clarify whether explosive muscle power depends only on the macroergic phosphate compounds or other factors, which can be influenced through specific training, are also involved, this study used a Wingate testing protocol to follow the evolution of anaerobic performance parameters in 450 top athletes trained for aerobic (70 athletes), anaerobic (224 athletes) and mixed events (156 athletes). Parameters studied were the Peak Power (PP), Time at Peak Power (TPP), correlations between them and Average Powers recorded on each 5-second interval of maximal effort. The results showed that TPP was shorter than 5 sec only for the alactacid anaerobic groups (3.630 sec for men and 3.960 sec for women), the other athletes reaching maximum power after 5 sec. Most athletes registered the highest average power in the second 5-second interval (5-10 sec) and not in the first one (0-5 sec), as expected, except for the alactacid anaerobic group. The anaerobic alactacid and mixed energogenesis groups achieved a significant negative correlation between PP and TPP (p< 0.05), these groups being composed of athletes whose specific training aimed to improve their neuro-motor skills and movement pattern. The results of this research show that explosive power depends on the muscle composition, but also confirms the importance of motor skills in improving the recruitment velocity of fast muscle fibres and muscle power generation.